2010
DOI: 10.1002/ejoc.200901216
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Enantiopure Benzyl Homoallylamines by Indium‐Mediated Barbier‐Type Allylation Combined with Enzymatic Kinetic Resolution: Towards the Chemoenzymatic Synthesis of N‐Containing Heterocycles

Abstract: Barbier-type indium-mediated allylations of different N,N-(dimethylsulfamoyl)-protected aldimines with a number of allyl bromides followed by high-yielding deprotection afforded allylic amines in good to excellent yields. The racemic amines were then subjected to enzymatic kinetic resolution in order to obtain the corresponding (S)-amines and (R)-amides. When acyl donors with a terminal double bond were applied in the enzymatic kinetic resolution, the product

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Molecular sieves were necessary, because the so‐called residual water in the seemingly dry enzyme catalyst or traces of water in the mixture may cause lipase‐catalyzed hydrolysis of hydrolyzable compounds. Under the present N ‐acylation conditions, the hydrolysis of an acyl donor may lead to ammonium salt formation between an amine and the acid liberated, lowering the enantioselectivity of the kinetic resolution 7d,17. The effect of water was clear when the N ‐acylation of rac ‐ 3a was performed in ethyl acetate saturated with water ( E = 50) compared to the reaction in anhydrous ethyl or isopropyl acetate ( E > 100; Table 1, Entries 1–3).…”
Section: Resultsmentioning
confidence: 99%
“…Molecular sieves were necessary, because the so‐called residual water in the seemingly dry enzyme catalyst or traces of water in the mixture may cause lipase‐catalyzed hydrolysis of hydrolyzable compounds. Under the present N ‐acylation conditions, the hydrolysis of an acyl donor may lead to ammonium salt formation between an amine and the acid liberated, lowering the enantioselectivity of the kinetic resolution 7d,17. The effect of water was clear when the N ‐acylation of rac ‐ 3a was performed in ethyl acetate saturated with water ( E = 50) compared to the reaction in anhydrous ethyl or isopropyl acetate ( E > 100; Table 1, Entries 1–3).…”
Section: Resultsmentioning
confidence: 99%
“…Although the Ellman group reported that allylmagnesium bromide was added from the Si -face of ( S )- tert -butylsulfinyl imine 17 to deliver 18 (ref 3a), the opposite configuration was later confirmed by the Nelson group (ref 3b). The Nelson group prepared ( R )-benzamide 19 from both the commercially available ( R )-2-amino-4-pentenoic acid ( 20 ) and using Ellman’s method with ( S )- tert -butanesulfinamide.…”
Section: References and Notesmentioning
confidence: 99%
“…2 In particular, δ-substituted α,β-unsaturated δ-lactams are widely encountered in biologically active molecules and thus, various methodologies have been developed for preparing enantioenriched δ-substituted α,β-unsaturated δ-lactams. 3 In addition, a considerable number of approaches to afford α-substituted α,β-unsaturated δ-lactams have been reported. 4 However, only few studies toward enantioenriched α,δ-disubstituted α,β-unsaturated lactams have been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last two decades, a new methodology using an enzyme as the resolution catalyst has been intensively developed for the synthesis of enantiomerically pure amines and their derivatives mainly via enzymatic hydrolysis, 11 aminolysis, 12 acylation, 13,14 and alkoxycarbonylation processes. 15 Enzyme-catalyzed methods have also shown their potential in the preparation of secondary amines.…”
Section: Introductionmentioning
confidence: 99%